Ru3(CO)12‐Catalyzed Modular Assembly of Hemilabile Ligands by C−H Activation of Phosphines with Isocyanates. (27th December 2022) - Lin, Lin; Zhang, Xue‐jun; Xu, Xinyu; Zhao, Yue; Shi, Zhuangzhi
Abstract: Hemilabile ligands have been applied extensively in transition metal catalysis, but preparations of these molecules typically require multistep synthesis. Here, modular assembly of diverse phosphine‐amide ligands, including related axially chiral compounds, is first reported through ruthenium‐catalyzed C−H activation of phosphines with isocyanate directed by phosphorus(III) atoms. High reactivity and regioselectivity can be obtained by using a Ru3 (CO)12 catalyst with a mono‐N‐protected amino acid ligand. This transformation significantly expands the pool of phosphine‐amide ligands, some of which have shown excellent efficiency for asymmetric catalysis. More broadly, the discovery constitutes a proof of principle for facile construction of hemilabile ligands directly from the parent monodentate phosphines by C−H activation with ideal atom, step and redox economy. Several dinuclear ruthenium complexes were characterized by single‐crystal X‐ray diffraction analysis revealing the key mechanistic features of this transformation. Abstract : A phosphorus(III)‐directed C−H aminocarbonylation of monodentate phosphines has been developed for modular assembly of bidentate hemilabile ligands. The use of mono ‐ N ‐protected amino acid (MPAA) ligands is crucial for the inhibition of catalyst poisoning.